A preliminary outlook of the textual and visual characteristics of fake news in Malaysian cyberspace: a case study of fake news posts on Facebook - Yeoh, Sarah Yu-En (2019)
Throughout the presidential campaign and subsequent election of Donald Trump in 2016, the term fake news has been mentioned for an unprecedented amount of times, prompting a social phenomenon which scholars have called ‘post-truth’ in a society where misinformation and downright falsity seem to hold greater regard over solid facts. Coupled with technological advancements, fake news has found a home within the cyberspace realm where it has been utilized by rightists/conservatives as a tool to either champion or demonize political ideologies that do not fall in line with its own. Although fake news is a relatively new concept in Malaysia, it continues to make its impact known namely through Facebook; paving the way for the Anti Fake News Act’s formulation in April last year. Given such circumstances, this research aims to study its textual and visual characteristics, the political ideologies embedded within it, and whether the political discourse in Malaysia is that of a conservative stance through the fake news posts disseminated on Facebook. Theoretical frameworks such as Stuart Hall’s Representation Theory and Roland Barthes’ concept on myths were employed in this study to provide a clearer picture into the mechanisms and purposes of fake news.